Determination of iFGF23 Upper Reference Limits (URL) in healthy pediatric population, for its better correct use - Brescia, Vincenzo; Fontana, Antonietta; Lovero, Roberto; Capobianco, Carmela; Marsico, Stella Vita; De Chirico, Tiziana; Pinto, Carla; Varraso, Lucia; Cazzolla, Angela Pia; Di Serio, Francesca (Frontiers in Endocrinology, 2022)
Background: The measurement of Fibroblast growth factor 23 (FGF23) may be useful in the diagnosis and management of abnormal phosphate metabolism in both patients with preserved renal function or with chronic kidney disease (CKD). FGF-23 tests differ considerably by molecule assayed (iFGF23 or cFGF23), analytical performance and reference ranges. We establish iFGF23 Upper Reference Limits (URL) in apparently healthy pediatric individuals using automated immunochemiluminescent assay. Methods: We measured the levels of plasma iFGF23 from 115 samples from apparently healthy pediatric subjects [59 (51.3%) individuals were male; median age 10 years (range 1–18)] included in an observational study conducted at Policlinico University Hospital of Bari. The method used for the iFGF23 assay was immunochemiluminescent sandwich assay developed by DiaSorin on the Liaison XL platform. Statistical calculation of 95% reference interval, right-sided (CLSI C28-A3) and verification of age and sex covariables was performed for the calculation of the URL. Results: The URL concentration of iFGF23 was 61.21 pg / mL (58.63 to 63.71, 90% CI). No significant differences were found between the median concentrations of iFGF23 differentiated by sex and age. Conclusions: The dosage of iFGF23 is important both for the differential diagnosis of the various forms of rickets, and for the subsequent monitoring of the effectiveness of drug treatment. We have established the URL for the iFGF23 Liaison test in apparently healthy pediatric subjects. The availability of iFGF23 pediatric reference values will allow a better clinical use of the test.